Search for tt¯H/A→tt¯tt¯ $$ t\overline{t}H/A→ t\overline{t}t\overline{t} $$ production in the multilepton final state in proton-proton collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Beyond Standard Model, Hadron-Hadron Scattering, Top Physics.; Springer Open.